International relations in the Middle East hegemonic strategies and regional order - Stein, Ewan (Cambridge University Press, 2020)
"Developing an original theoretical approach to understanding the roots of regional conflict and cooperation, International Relations in the Middle East explores domestic and international foreign policy dynamics for an accessible insight into how and why Middle Eastern regional order has changed over time. Highlighting interactions between foreign policy trajectories in a range of states including Egypt, Iran, Iraq, Israel, Saudi Arabia, Syria and Turkey, Ewan Stein identifies two main drivers of foreign policy and alignments: competitive supportseeking and ideological externalisation. Clearly linking political, ideological and foreign policy dynamics, Stein demonstrates how the sources of regional antagonisms and solidarities are to be found not in the geopolitical chessboard, but in the hegemonic strategies of the region's pivotal powers. Making the case for historical sociology- in particular the work of Antonio Gramsci and Louis Althusser-as the most powerful lens through which to understand regional politics in the Middle East, with wider implications for the study of regional order elsewhere"--